Plasma Matrix Metalloproteinase-9 Level Is Better than Serum Matrix Metalloproteinase-9 Level to Predict Gastric Cancer Evolution - Wu, Chun-Ying; Wu, Ming-Shiang; Chiang, En-Pei; Chen, Yi-Ju; Chen, Chien-Jen; Chi, Nai-Hui; Shih, Ying-Ting; Chen, Gran-Hum; Lin, Jaw-Town (Clinical cancer research, 2007)
Purpose: Matrix metalloproteinase-9 (MMP-9) in blood is a promising new tumor marker. The aims of the present study are to compare the usefulness of plasma and serum MMP-9 levels for predicting gastric cancer development, invasion, and survival. Experimental Design: In this nested case-control study, 114 gastric cancer patients and 87 healthy controls were enrolled. MMP-9 levels and activities were quantitatively measured by ELISA assay and zymography. The results were compared with the occurrence, clinicopathologic features, and outcomes of gastric cancer patients. The follow-up time for all patients was at least 5 years. Results: Serum MMP-9 levels were significantly higher than plasma MMP-9 levels. Both plasma and serum MMP-9 levels correlated significantly with active MMP-9 identified by zymography ( P = 0.002 and P = 0.048, respectively). Plasma MMP-9 level was significantly elevated in gastric cancer patients when compared with control subjects ( P < 0.001). Serum MMP-9 levels did not differ between the groups. Receiver-operator characteristics analysis showed the values of sensitivity (82.5%) and specificity (65.5%) at the maximum accuracy for plasma MMP-9 at ≥60 ng/mL ( P < 0.001). Elevated plasma MMP-9 correlated significantly with lymph node metastasis [odds ratio (OR), 3.43; P = 0.019], lymphatic invasion (OR, 7.58; P = 0.009), and venous invasion (OR, 4.14; P = 0.033). Patients with elevated plasma MMP-9 levels had poorer survival rates than those with normal plasma MMP-9 levels ( P = 0.038). Serum MMP-9 level did not correlate well with gastric cancer–invasive phenotypes or survival. Conclusion: Our results suggest plasma MMP-9 level is a better marker than serum MMP-9 level for predicting gastric cancer development and progression.